Les impacts hydrologiques de la production de neige dans un domaine de moyenne montagne - Élodie Magnier (VertigO)
Artificial snowmaking is a relatively recent practice in Europe and in North America. This activity is necessary for the ski resorts to maintain and develop economic activities. However snowmaking requires large quantities of water, which are pumped from rivers, groundwater, drinking water reserves, artificial hydropower reservoirs and hill water reservoirs. It is estimated that 4000 m3 of water can cover one hectare. Moreover, snowmaking does not represent the only use of water in winter sport resorts (drinking water, activities...). The problem raised here is availability of water for these various activities during the winter season. The aim of this study is to measure the impact of water extraction for artificial snowmaking on the variations in the available resource at the local scale in a three French and Swiss ski resorts (Avoriaz, Champéry, Les Gets), and to identify two risk situations for the resorts: risks of resources used conflicts and risks of water shortages. In these resorts, the mobilization of a large volume of water over a very short period makes water management an issue that can create risk situations. Intensity of use for the snow production can have impacts on other uses. This study showed also that the sharing of the resource it's a risky situation, particularly when a unique lake or hillside reservoir permits the water supply for production of snow and drinking water. Situations of water shortage can exist punctually and the situation needs to be monitored.